Emotional intelligence increases the spiritual intelligence of organizational employees - Mohd Lokman Sapiee; Nurul Azza Abdullah; Fatima Wati Halim; Arena Che Kasim; Nurshahira Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research aims to investigate the link between intelligence (including selfmanagement, social awareness and relationship management) and spiritual intelligence within an organizational body in Malaysia. A group of 100 participants completed a questionnaire for the study. The analysis was conducted using SmartPLS software to examine the questionnaire responses and test the research hypotheses. The results revealed a positive and significant correlation between self-management, social awareness and relationship management in emotional intelligence and employees’ spiritual intelligence. These findings highlight the role of emotional intelligence components, specifically self-management, social awareness and relationship management in shaping employees’ spiritual intelligence. This study contributes to enhancing practitioners’ understanding of how emotional intelligence can elevate employee’s spiritual well-being. It offers perspectives on enhancing employees’ emotional control abilities to boost their development for long-term sustainability. Moreover, it provides insights for crafting strategies to navigate challenges effectively.